Law Enforcement Against Children as Perpetrators of Aggravated Theft Committed Jointly: A Case Study of Decision Number: 26/Pid.Sus-Anak/2020/PN.Son - Ari Iswandy Sihombing; Janpatar Simamora; Jusnizar Sinaga (Universitas Islam Negeri Alauddin Makassar, 2026)
This study analyzes the criminal liability of children as perpetrators of theft with joint aggravation and the judge’s legal considerations in Decision Number 26/Pid.Sus-Anak/2020/PN.Son. The research is motivated by the increasing involvement of children in serious crimes, which raises normative tension between the principle of ultimum remedium in juvenile justice and the practical tendency to impose imprisonment, particularly in cases involving aggravating circumstances or recidivism. Within the framework of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, law enforcement is required to prioritize protection, rehabilitation, and the best interests of the child. This study employs a normative juridical method using statutory and case approaches, focusing on the application of Article 363 paragraph (2) of the Criminal Code and relevant provisions governing juvenile criminal responsibility. The findings indicate that the elements of aggravated theft committed jointly were legally fulfilled, thereby establishing the child’s criminal liability. The judge imposed a sentence of one year and six months’ imprisonment based on juridical considerations, evidentiary facts, and the child’s personal circumstances, while formally referring to the principle of the best interests of the child. The contribution of this research lies in evaluating the consistency of judicial reasoning in applying the best interests principle in aggravated theft cases involving children, as well as assessing whether the decision reflects proportionality, legal certainty, and substantive justice within the juvenile criminal justice system.